Responding to Structural Shocks: Hadith of the Prophet and the Social Resilience of Early Islamic Communities - Halimi Najeeb Alkhawlani; Aljohani Mousa Qashqary; Mohamed Ibrahim Rejab; Abdelrazek Hasan bin Zawawi; Siti Najihah binti Mahmud (Hamidah: Jurnal Ilmu Hadis, 2026)
Structural shocks—such as economic crises, social conflicts, and political disruptions—are historical realities that shaped the dynamics of early Islamic communities. However, hadith studies are still dominated by normative, partial readings, thus inadequate for comprehensively explaining collective responses to crises. This study aims to construct a conceptual framework for hadith-based social resilience by analyzing the representation of structural shocks, collective response patterns, and resilience mechanisms of early Islamic communities. This study uses a qualitative approach based on literature reviews, employing thematic-contextual analysis of hadiths selected for their relevance to social crises, which are then classified, coded, and interpreted through socio-historical readings to reconstruct the contexts in which they emerged. The results show that hadiths can be classified into three main patterns of social resilience: First, crisis identification through disruption indicators such as distribution inequality, internal conflict, and vulnerability of marginalized groups; second, collective response strategies that include strengthening solidarity, redistributive obligations (such as zakat and ṣadaqah), and community-based social protection mechanisms; Third, an adaptive prophetic leadership model characterized by situational responsiveness, moral legitimacy, and an orientation toward long-term stability. These findings confirm that the hadith serves as a structured normative-strategic framework for building social resilience. This research expands the approach to hadith studies toward an integrative-contextual reading and offers conceptual contributions to the development of social resilience studies from an Islamic perspective.